2021
DOI: 10.21873/invivo.12253
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Activates ROS Signaling to Promote Pyroptosis in Hepatocellular Carcinoma HepG2 Cells

Abstract: Background/Aim: Curcumin is a polyphenol that exerts a variety of pharmacological activities and plays an anti-cancer role in many cancer cells. It was recently reported that gasdermin E (GSDME) is involved in the progression of pyroptosis. Materials and Methods: HepG2 cells were treated with various concentrations of curcumin and cell viability was examined using MTT assay, apoptosis was analysed using flow cytometry, reactive oxygen species (ROS) levels using dihydroethidium, LDH release using an LDH cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…Interleukin-1β (IL-1β), an important mediator of inflammatory response after ischemia-reperfusion, could induce the synthesis of other inflammatory factors, chemokines and adhesion molecules, etc. The cascade magnification reaction, which causes pathological inflammatory response, is an important “executor” of cell pyroptosis-induced cell inflammatory death ( Liang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin-1β (IL-1β), an important mediator of inflammatory response after ischemia-reperfusion, could induce the synthesis of other inflammatory factors, chemokines and adhesion molecules, etc. The cascade magnification reaction, which causes pathological inflammatory response, is an important “executor” of cell pyroptosis-induced cell inflammatory death ( Liang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Liping Chen et al 21 found that the curcumin derivative exhibited good anti-tumor activity both in vitro and in vivo via the switch of apoptosis-to-pyroptosis. Wan-Feng Liang 10 found that curcumin activates ROS signaling to promote pyroptosis in hepatocellular carcinoma HepG2 cells. In our studies, we found that heterologously overexpressing GSDMD enhanced sensitivity of K562 cell to curcumin, and inhibition of GSDMD with shRNA in U937 cells enhance curcumin anti-leukemia effect, indicating that the sensitivity of leukemia cells to curcumin is clearly related to pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 7–9 Recent studies have found that curcumin can induce pyroptosis of solid tumor cells. 10 , 11 However, it is not clear whether pyroptosis is involved in the anti-leukemia effect of curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…1A ), a polyphenolic compound, is the principal curcuminoid derived from the rhizomes of turmeric ( 12 ); it is able inhibit lipopolysaccharide-induced NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome, thereby inhibiting the activation of IL-1β and caspase-1 ( 13 , 14 ). In addition, curcumin also exhibits antioxidant and anti-tumor properties ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%